Surveilans Berbasis Santri : Strategi Meningkatkan Derajat Kesehatan di Pondok Pesantren - Joni, Joni; Gustaman, Rian Arie; Setiyono, Andik; Marlina, Lina; Ulfah Khofifah, Sari; Destiati, Dita (Jurnal Abdimas Jatibara, 2024)
Community-based surveillance is a health effort to identify health problems/cases carried out by the community, which is then addressed by the community with the support of healthcare workers. This activity is one of the self-reliance patterns instilled in the community. Indonesia has more than 20,000 pesantrens as formal educational institutions. Unhealthy environments and inadequate facilities have led to various infectious diseases. Efforts to examine and treat infectious diseases have been carried out by pesantrens, but the problem persists due to unhealthy behavior. Health monitoring and responsibility from pesantren residents are necessary to improve health conditions in pesantrens. Based on this issue, community-based surveillance needs to be implemented in pesantrens. Empowering pesantren communities is a process to increase knowledge, awareness, and skills so that they can actively participate in efforts to prevent and control diseases through an educative and participatory approach while considering potential needs and local socio-cultural aspects. Therefore, a trained Santri-based Surveillance needs to be formed with the responsibility of health monitoring in pesantrens, in the hope of creating a healthy pesantren. Santri-based surveillance is part of community empowerment in pesantren areas